Ergonomic stressors and upper extremity musculoskeletal disorders in automobile manufacturing: a one year follow up study. Issue 8 (16th July 2004) - Punnett, L; Gold, J; Katz, J N; Gore, R; Wegman, D H
Abstract : Aims: To estimate the one year cumulative incidence and persistence of upper extremity (UE) soft tissue disorders, in a fixed cohort of automotive manufacturing workers, and to quantify their associations with ergonomic exposures. Methods: At baseline and at follow up, cases of UE musculoskeletal disorders were determined by interviewer administered questionnaire and standardised physical examination of the upper extremities. The interview obtained new data on psychosocial strain and updated the medical and work histories. An index of exposure to ergonomic stressors, obtained at baseline interview, was the primary independent variable. Cumulative incidence and persistence of UE disorders (defined both by symptoms and by physical examination plus symptoms) were analysed in relation to baseline ergonomic exposures, adjusting for other covariates. The incidence of new disorders was modelled using multivariate proportional hazards regression among workers who were not cases in the first year and the prevalence on both occasions was modelled by repeated measures analysis. Results: A total of 820 workers (69% of eligible cohort members) was examined. Follow up varied slightly by department group but not by baseline exposure level or other characteristics. Among the non-cases at baseline, the cumulative incidence of UE disorders was 14% by symptoms and 12% by symptoms plus examination findings. These rates increased with index of physical exposures primarily among subjects who had the same jobs at follow up as at baseline. Increased exposure during follow up increased risk of incidence. The persistence of UE disorders from baseline to follow up examination was nearly 60% and somewhat associated with baseline exposure score. Conclusions: These longitudinal results confirm the previous cross sectional associations of UE musculoskeletal disorders with exposure to combined ergonomic stressors. The exposure-response relation was similar for incident cases defined by symptoms alone and those confirmed by physical examination.